The relationship between motivational factors and job performance among employees at Sarawak Energy Berhad (SEB) in Kuching, Sarawak / Mary Loreta Ah Sen - Ah Sen, Mary Loreta (2017)
Motivation has been identified as important elements to help employees contribute greater job performance. This study was focused on examining the relationship between motivational factors and job performance. Three motivational factors that involved in this study includes salary, promotion and job security. A total of 132 respondents from various department at Sarawak Energy, Kuching, Sarawak involved in this study. Pilot test has been carried out at Risda in Samarahan Division to test the reliability of the questionnaire. Result of the Pearson Correlation analyses showed there was a significant relationship between promotion and job performance, and between job security and job performance. Correlation analysis showed that there was a strong relationship between job security and job performance. These results were believed to provide new finding to the field of study.